Posttranslational modification of class III beta-tubulin. - Lee, M K (1990)
The charge heterogeneity of class III beta-tubulin (beta III) during neural development was analyzed by high-resolution isoelectric focusing/two-dimensional polyacrylamide gel electrophoresis in combination with site-specific proteolytic digestion and immunological detection. The number of beta III isoforms (charge variants) gradually increases from one in embryonic brain to seven in adult brain. All of the charge heterogeneity is due to posttranslationally modified sites located within the extreme C-terminal region of the beta III polypeptide. One beta III isoform is present in testis, the only other tissue in which this isotype is expressed. The testis beta III isoform cofocuses with the earliest-appearing embryonic brain beta III charge variant. Our results indicate that the posttranslational modifications of beta III are developmentally regulated, occur at more than one site, and are neuron-specific. The location of these modifications within the extreme C-terminal domain suggests that their function is to modulate the interaction of tubulin with microtubule-associated proteins.